Nursing professionals' mental well‐being and workplace impairment during the COVID‐19 crisis: A Network analysis. (1st March 2021) - Tokac, Umit; Razon, Selen
Abstract: Aim: To investigate the effects of years of nursing experience and mental health on work impairment among nurses during the COVID‐19 crisis. Background: During the COVID‐19 crisis, nurses experience a greater psychological burden than other health care workers. Studies have not yet investigated the effects of years in nursing and mental health on potential work impairment during the COVID‐19 crisis in nurses. Methods: A survey was administered to 83 nurses on active duty during the COVID‐19 crisis. The graphical LASSO and the DAG helped estimate the associations between years of nursing experience, mental health and work impairment. Results: A moderate negative correlation emerged between years of nursing experience, avoidance and work impairment. A direct effect was observed between anxiety and work impairment. A moderate positive correlation emerged between anxiety, depression and work impairment. An indirect effect was observed between depression, burnout, insomnia, years of nursing experience and work impairment. Conclusions: In the present sample, nurses' work impairment decreased with greater years of nursing experience and increased with higher anxiety, depression, burnout and avoidance levels. Implications for Nursing Management: These findings can help design effective infectious disease management programmes for students and professionals in nursing to prevent breakdowns and avoid work impairment.